MEDIA COMPIC (COMPUTERIZED PICTOGRAPH) UNTUK MENINGKATKAN AKTIVITAS BELAJAR ANAK AUTIS HIPERAKTIF - Qomaroh, Alimatul (Jurnal Pendidikan Khusus, 2016)
ABSTRACT The research problem is if there is an improvement of the learning activity by using compic for the hyperactive children with autism at second grade of Dharma Wanita School for special needs children Ujungpangkah Gresik. This research uses experimental research by using Single Subject Research. Based on the result of visual analysis in the baseline phase, it shows the unstable condition, while in the intervention phase shows the stable changes. The visual analysis between conditions in the baseline phase to intervention phase is decresing or getting better which shows that the change is positive. Therefore, it can be concluded that compic (computerized pictograph) affects the learning activities of the hyperactive children with autism positively.   Keywords : compic media, hyperactive behavior